High and Low Activity Spells in Housing Markets - Eric Smith (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper demonstrates the way in which stock-flow matching with endogenous seller entry generates hot and cold spells in house sales. Potential sellers know the number of bidders remaining from the last house sale. If two or more bidders remain, the seller obtains the gains to trade through competitive bidding. The market is active. With one monopolistic bidder, the buyer captures the surplus and sellers become unwilling to enter. The market remains dormant until sellers think enough time has passed for buyer entry to have replenished the market and make entry profitable. The resulting pattern of trade matches up with observations from Wisconsin.
Keywords: R31; D53; 330; trading volume; stock-flow matching; house price dynamics